Fungistatic activity and mechanism of Caulerpa racemosa, Caulerpa lentillifera fractions and caulerpin metabolite against pathogenic fungi - Nursidika, Perdina; Julianti, Elin; Kurniati, Neng F. (Narra J, 2025)
The increasing prevalence of azole resistance in various fungal species presents a significant concern, highlighting the urgent need for new antifungal agents. The aim of this study was to investigate the antifungal activity of fractions from Caulerpa racemosa, C. lentillifera, and caulerpin against three species: Aspergillus flavus, A. niger, and Candida albicans. The Caulerpa extracts were obtained through maceration with 96% ethanol, followed by fractionation using vacuum liquid chromatography. Antifungal activity was assessed using the broth microdilution method, while fungal growth kinetics were evaluated through time-kill curves. Bioautography was employed to identify inhibitory compounds, while liquid chromatography high-resolution mass spectrometry (LC-HRMS) was utilized to detect the contents of the extracts and fractions. Scanning electron microscopy (SEM) was used to observe the fungal structure, and the absorbance at 260/280 nm was measured to evaluate the cell leakage. LC-HRMS identified numerous compounds in C. racemosa and C. lentillifera with antifungal activities, including fatty acids, terpenes, alkaloids, flavonoids, and coumarins. The results indicate that the fractions of both Caulerpa did not inhibit the growth of A. flavus and A. niger, but effectively inhibited C. albicans. Among the fractions, F3CR and F4CL exhibited the highest antifungal efficacy against C. albicans, with minimum inhibitory concentrations (MICs) ranging from 64 to 128 µg/mL. Caulerpin, the primary metabolite of Caulerpa, also demonstrated significant inhibition, with an MIC of 256 µg/mL. The findings suggested that F3CR, F4CL, and caulerpin possessed fungistatic properties. Bioautography results revealed clear zones in the colonies, indicating inhibited fungal growth. The SEM observations showed that fungal cells became rough, perforated, and damaged, which was confirmed by the increase in absorbance at 260/280 nm, suggesting the release of cellular components such as nucleotides and proteins. In conclusion, both Caulerpa species and caulerpin are promising candidates for developing new antifungal agents against C. albicans.